A autenticidade e a organicidade nos acervos fotográficos do patrimônio documental à luz da diplomática contemporânea - Souza, Marcieli Brondani de (2016)
This research sought to analyze, based on the principles of Contemporary Diplomatic, elements and characters that allow to guarantee the authenticity and the organicity in the photographic collections of documentary heritage. For a long time the photographs were treated as documents belonging to special files, as needed to be stored in different places than where the text documents were kept considering its specific support, and received differentiated technical treatment from the other documents. Due to this physical separation, the photographs did not receive a proper archival treatment, becoming mere document accumulated masses, affecting their organic relations and authenticity. Currently, with the facilities provided by the use of digital technologies, the situation of photographic collections can be even more compromised. The photos are produced and disseminated quickly in digital media, and can easily lose its identity, its origin, its organicity and all the information that should remain linked to it, hurting its authenticity this way. The research was conducted under two Federal Institute of Superior Education (UFAM and UFSM), where interviews were conducted with the producers of photos and sent questionnaires to the central archives of the institutions, using e-sic, to understand how to give the archival processing of photographs. This research is characterized as exploratory, from the objective point of view and has qualitative and applied nature approach. The organicity and authenticity nature of the photographs belonging to the archival document heritage are closely linked to the treatment to be given to them throughout their life cycle. Therefore, the analysis and discussion of the results was based on three axes considered fundamental to ensure the authenticity and organicity of the photographic collections of cultural heritage: the maintenance of chain of custody of digital photographs with the use of reliable systems to provide management and the archival management of digital photos; the understanding of the specificity and complexity of digital archival documents, aiming to propose performing procedures to properly handle photographs as digital archival documents; the inclusion of photographs in the document management programs of institutions according to Resolution 41, recently published by CONARQ. It was stated that the control of the production of photographs, the correct storage, preservation of the characteristics of archival documents, the adequacy of the classification plans to contemplate the photos, assigning codes to photos while in production, carrying out elimination procedures based on the evaluation of documents and the execution of all these procedures using archival management information systems that follow the requirements of e-ARQ Brazil avoid the appearance of accumulated document mass and the break-up of sets of documents, ensuring that photographs keep their organic relations, and remain whole and authentic. The achievement of the objective of this research, made possible the formulation of recommendations to ensure the authenticity and the organic in the collections of documentary heritage, focused to photograph production sectors of the institutions and central archives that define policies for these sectors. Please note that this research, a pioneer in its context, must be expanded in order to include all issues related to the chain of custody and management of digital archival documents associated to photography.